Tectonic and climatic controls on the Chuquibamba landslide (western Andes, southern Peru) - Margirier, Audrey (2015)
The contribution of landslides to the Quaternary evolution of relief is poorly documented in arid contexts. In southern Peru and northern Chile, several massive landslides disrupt the arid western Andean front. The Chuquibamba landslide, located in southern Peru, belongs to this set of large landslides. In this area, the Incapuquio fault system captures the intermittent drainage network and localizes rotational landslides. Seismic activity is significant in this region with recurrent Mw 9 subduction earthquakes; however, none of the latest seismic events have triggered a major landslide. New terrestrial cosmogenic dating of the Chuquibamba landslide provides evidence that the last major gravitational mobilization of these rotational landslide deposits occurred at ~ 102 ka, during the Ouki wet climatic event identified on the Altiplano between 120 and 98 ka. Our results suggest that wet events in the arid and fractured context of the Andean forearc induced these giant debris flows. Finally, our study highlights the role of tectonics and climate on (i) the localization of large Andean landslides in the Western Cordillera and on (ii) the long-term mass transfer to the trench along the arid Andean front.